2D Materials: 2D Tin Monoxide—An Unexplored p‐Type van der Waals Semiconductor: Material Characteristics and Field Effect Transistors (Adv. Electron. Mater. 4/2016). (April 2016) - Saji, Kachirayil J.; Tian, Kun; Snure, Michael; Tiwari, Ashutosh
Abstract : Growth of a new van der Waals material—2D Tin Monoxide (SnO)—by using a pulsed laser deposition technique is reported by A. Tiwari and coworkers in article number 1500453. Such materials are promising candidates for developing next generation electronic devices. In their article, the authors demonstrate that the number of SnO monolayers can be precisely controlled by controlling the number of laser pulses during the deposition process.